Status of ground motion mitigation techniques for clic - Snuverink, J; Artoos, K; Collette, C; Ramos, F; Gaddi, A; Gerwig, H; Janssens, S; Pfingstner, J; Schulte, D; Resta-Lopez, J; Balik, G; Brunetti, L; et al. (2011)
The Compact Linear Collider (CLIC) accelerator has strong stability requirements on the position of the beam. In particular, the beam position will be sensitive to ground motion (GM). A number of mitigation techniques are proposed - quadrupole stabilisation and positioning, final doublet stabilisation as well as beam-based orbit and interaction point (IP) feedback. Integrated studies of the impact of the GMon the CLIC Main Linac (ML) and Beam Delivery System (BDS) have been performed, which model the hardware and beam performance in detail. Based on the results, future improvements of the mitigation techniques are suggested and simulated. It is shown that with the current design the tight luminosity budget for GM effects is fulfilled and accordingly, an essential feasibility issue of CLIC has been addressed. Copyright © 2011 by IPAC'11/EPS-AG.